Fire-proof, short-circuit-proof and aging-proof electric wire and cable

By using a copper body to coat the ceramic silicone layer in the wire and cable, and covering it with a modified PVC material layer, the problems of flammable, low temperature resistance and easy aging during overload or aging short circuit are solved, and multiple properties of wire and cable are achieved, which extends the service life.

CN118762871BActive Publication Date: 2025-03-28ZHEJIANG OPPO CABLE CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411140785.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-03-28
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

When existing wires and cables are overloaded or aging short-circuited, the plastic insulation layer is flammable, has low temperature resistance and is prone to aging, causing the conductor to heat and melt the insulation layer, generating short-circuit sparks and causing spontaneous combustion of the wires.

Method used

The ceramic silicone layer was coated with a copper body and a modified PVC material layer was coated on the ceramic silicone layer. The modified PVC material was prepared by reacting cerium/lanthanum doped titanium oxide/alumina nanomaterial with phenylphosphoryl dichloride, and adding PVC material to melt blend.

Benefits of technology

It realizes the fireproof, short circuit, flame retardant, high temperature resistance, ultraviolet aging, hydrophobic and oleophobic, tensile resistance, wear resistance, antibacterial and insect resistance of wires and cables, extending service life and improving durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005000725480000131
    Figure BDA0005000725480000131
  • Figure BDA0005000725480000141
    Figure BDA0005000725480000141
Patent Text Reader

Abstract

The present invention proposes a fireproof, short-circuit-proof and aging-proof wire and cable, belonging to the technical field of wire and cable. It comprises a copper body, a ceramic silica gel layer coated on the copper body, and a modified PVC material layer coated on the ceramic silica gel layer, wherein the ceramic silica gel layer is made by sintering a silica sol modified by silicon nitride and a sintering aid and adhering to the surface of ceramic fiber paper; the modified PVC material layer is made by modifying the surface of cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterials by a silane coupling agent, reacting with phenylphosphoryl dichloride, and adding PVC material for melt blending. The fireproof, short-circuit-proof and aging-proof wire and cable prepared by the present invention has good fireproof, short-circuit-proof, flame-retardant, high temperature resistance, UV aging resistance, hydrophobic and oleophobic, tensile resistance, wear resistance, antibacterial and insect-proof, long service life, good durability, and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electric wires and cables, and in particular to a fire-proof, short-circuit-proof and aging-proof electric wire and cable. Background Art

[0002] Cables are widely used in power, communications and related transmission projects. They are usually rope-like cables composed of several or several groups of wires, with at least two wires in each group twisted together. Each group of wires is insulated from each other and often twisted around a center wire. The entire outside is covered with a highly insulating covering.

[0003] The power wires currently used in the market are all wrapped with a layer of plastic insulation around the conductor. The plastic insulation layer has good insulation performance, but it is a flammable material with low temperature resistance and easy aging. When the line is overloaded or aging short-circuited, the high temperature generated by the heat of the conductor melts the plastic insulation layer, causing a short-circuit spark between the zero and phase conductors in the sheathed wire, igniting the melted plastic insulation layer and causing the wire to spontaneously combust. Summary of the invention

[0004] The purpose of the present invention is to provide a fireproof, short-circuit-proof and aging-proof electric wire and cable, which has excellent fireproofing, short-circuit-proofing, flame retardancy, high temperature resistance, resistance to ultraviolet aging, hydrophobicity and oleophobicity, tensile strength, wear resistance, antibacterial and insect resistance, long service life, good durability, and has broad application prospects.

[0005] The technical solution of the present invention is achieved in this way:

[0006] The invention provides a fireproof, short-circuit-proof and aging-proof electric wire and cable, comprising a copper body, a ceramic silica gel layer coated on the copper body, and a modified PVC material layer coated on the ceramic silica gel layer; the ceramic silica gel layer is prepared by adhering silica sol modified by silicon nitride and a sintering aid on the surface of ceramic fiber paper and sintering; the modified PVC material layer is prepared by modifying the surface of a cerium / lanthanum-doped titanium oxide / aluminum oxide nano material by a silane coupling agent, reacting the modified surface with phenylphosphoryl dichloride, and adding a PVC material for melt blending.

[0007] As a further improvement of the present invention, the preparation method of the ceramic silica gel is as follows:

[0008] S1. Modification of silicon nitride: adding silicon nitride powder to an acid solution, stirring the reaction, ball milling to obtain a grinding slurry, spray drying, and obtaining a modified silicon nitride powder;

[0009] S2. Preparation of modified silica sol: dissolving tetraethyl orthosilicate in ethanol, adding the modified silicon nitride and sintering aid obtained in step S1, adding water dropwise, stirring and hydrolyzing to form a modified silica sol;

[0010] S3. Preparation of ceramic silica gel: Immerse the ceramic fiber paper in the modified silica sol obtained in step S2, take it out after it is completely soaked, dry it, and repeat the soaking, taking it out, drying it, and sintering it to obtain ceramic silica gel.

[0011] As a further improvement of the present invention, the acid solution in step S1 is an ethanol solution containing 10-15wt% hydrochloric acid or sulfuric acid, the stirring reaction temperature is 35-45°C, the time is 0.5-1h, and the ball milling time is 1-2h.

[0012] As a further improvement of the present invention, the mass ratio of tetraethyl orthosilicate, ethanol, modified silicon nitride, sintering aid and water in step S2 is 12-15:200:3-5:0.5-1:15-20, the stirring hydrolysis temperature is 40-50°C, the time is 5-7h, and the sintering aid is alumina and silicon carbide, and the mass ratio is 4-7:2.

[0013] As a further improvement of the present invention, the ceramic fiber paper in step S3 is 90-110 g / m 2 Repeat the impregnation until the fiber paper reaches 130-150g / m 2 The sintering temperature is 800-1000°C and the sintering time is 2-4h.

[0014] As a further improvement of the present invention, the preparation method of the modified PVC material is as follows:

[0015] T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: dissolving cerium salt and lanthanum salt in water, adding to an ethanol solution containing tetrabutyl titanate and aluminum isopropoxide, stirring for reaction, ball milling, spray drying, and calcining to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials;

[0016] T2. Modification: adding the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial obtained in step T1 to water, adding a composite silane coupling agent, heating and stirring the reaction, centrifuging, washing, and drying to obtain a modified nanomaterial;

[0017] T3 flame retardant modification: the modified nanomaterial obtained in step T2 is added to dichloromethane, phenylphosphoryl dichloride is added dropwise, the reaction is heated and stirred under inert gas protection, centrifuged, washed, and dried to obtain a flame retardant modified nanomaterial;

[0018] T4. Preparation of modified PVC material: melt-blending the flame-retardant modified nanomaterial obtained in step T3 and PVC resin, extruding and granulating, to obtain a modified PVC material.

[0019] As a further improvement of the present invention, the cerium salt in step T1 is selected from at least one of cerium chloride and cerium nitrate, the lanthanum salt is selected from at least one of lanthanum chloride and lanthanum nitrate, the mass ratio of the cerium salt, lanthanum salt, tetrabutyl titanate, and aluminum isopropoxide is 0.5-1:0.2-0.4:12-15:7-10, the stirring reaction temperature is 30-40°C, the time is 2-4h, the ball milling time is 1-2h, and the calcination temperature is 400-600°C, and the time is 1-3h.

[0020] As a further improvement of the present invention, the mass ratio of the cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterial and the composite silane coupling agent in step T2 is 100:7-10, the composite silane coupling agent includes a long-chain alkyl silane coupling agent and a silane coupling agent with an amino group, the long-chain alkyl silane coupling agent is selected from at least one of dodecyl methoxy silane, dodecyl ethoxy silane, tetradecyl methoxy silane, tetradecyl ethoxy silane, hexadecyl ethoxy silane, and octadecyl ethoxy silane, the silane coupling agent with an amino group is selected from at least one of KH550, KH602, and KH792, preferably, the composite silane coupling agent is a mixture of octadecyl ethoxy silane and KH792, the mass ratio is 7-10:12-15, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-3h.

[0021] As a further improvement of the present invention, the mass ratio of the modified nanomaterial and phenylphosphoryl dichloride in step T3 is 100:3-5, the temperature of the heating and stirring reaction is 55-65°C, and the time is 5-7h; the mass ratio of the flame retardant modified nanomaterial and PVC resin in step T4 is 12-15:150, the temperature of the melt blending is 250-270°C, and the time is 1-3h.

[0022] As a further improvement of the present invention, the thickness of the ceramic silicone layer is 1.5-2.5 mm, and the thickness of the modified PVC material layer is 1-2 mm.

[0023] The present invention has the following beneficial effects:

[0024] The present invention prepares a ceramic silica gel material. First, silicon nitride powder is modified. Acid treatment is performed to dissolve the coated oxide layer and metal impurity ions on the surface of the silicon nitride powder to perform modification and purification. Then, the grinding slurry after ball milling is injected into a spray granulation tower, atomized into tiny droplets by high-speed centrifugation, and the solvent is volatilized in hot air, the powder is dried, and the sedimentation is collected to obtain modified silicon nitride powder. Sintering aids are added to improve the high temperature flame retardant performance of the material on the one hand, and at the same time, the mechanical properties of the ceramic silica gel are improved. Silicon nitride ceramics have the characteristics of high temperature resistance, high specific strength, high toughness, excellent wear resistance, etc., and still show relatively stable physical and chemical properties and long service life in extreme service environments. The modified silicon nitride powder prepared by the present invention has a high α-Si3N4 phase content, fine particle size and narrow particle size distribution, and has good sintering activity; low metal impurity ion content can significantly improve the high temperature resistance and mechanical properties of the material.

[0025] Add modified silicon nitride and sintering aids to an ethanol solution of ethyl orthosilicate, hydrolyze to obtain modified silica sol, add ceramic fiber paper, make the modified silica sol adhere to the ceramic fiber paper, and sinter to obtain ceramic silica gel with high surface strength. Wrapped on the surface of the copper body, it has good fireproof, short-circuit-proof, flame-retardant effects, and also has insulation properties. The synergistic effect of the sintering aid can significantly improve the hardness and flame-retardant properties of the material and reduce the vibration shedding rate.

[0026] Rare earth cerium ions and lanthanum ions have an unfilled 4f electron layer structure, so they have rich electronic energy levels and a relatively large ion radius. Cerium ions and lanthanum ions doped in titanium oxide / aluminum oxide nanomaterials can significantly improve the catalytic activity of titanium oxide, and have a synergistic effect, so that it also has a good catalytic effect in the visible light region, greatly improving the anti-ultraviolet, antibacterial and anti-aging properties of the modified PVC material doped with cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials. At the same time, the doping of alumina also improves the flame retardant properties of the modified PVC material.

[0027] The surface is further modified by a composite silane coupling agent, which includes a long-chain alkyl silane coupling agent and a silane coupling agent with an amino group. The long-chain alkyl silane coupling agent modifies the modified nanomaterial so that the surface of the nanomaterial has a long-chain alkyl group, which can be entangled with the PVC molecular chain, thereby improving the dispersibility of the nanomaterial in the PVC matrix, thereby achieving a good modification effect; at the same time, the long-chain alkyl silane coupling agent can also improve the hydrophobic and oleophobic properties of the PVC material; after the modified nanomaterial is further modified by the silane coupling agent with an amino group, the surface of the nanomaterial has an amino group, which can react with phenylphosphoryl dichloride, thereby obtaining a flame-retardant modified nanomaterial, which significantly improves the flame-retardant properties of the PVC material.

[0028] Therefore, the modified PVC material prepared by the present invention has good antibacterial, anti-ultraviolet, anti-aging, flame retardant properties, good waterproof and oil-proof effects, good mechanical properties, can well resist rat and insect bites, is coated on the outer layer of wires and cables, improves the service life of wires and cables, and has good durability.

[0029] The fireproof, short-circuit-proof and aging-proof electric wire and cable prepared by the present invention comprises a copper body, a ceramic silicone layer coated on the copper body, and a modified PVC material layer coated on the ceramic silicone layer. The electric wire and cable has excellent fireproofing, short-circuit-proofing, flame retardancy, high temperature resistance, UV resistance and aging resistance, hydrophobicity and oleophobicity, tensile strength, wear resistance, antibacterial and insect resistance, long service life, good durability, and has broad application prospects. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Ceramic fiber paper, made of aluminum silicate ceramic fiber, with a loss on ignition rate of <8%, a tensile strength of >400 kPa, and a thickness of 2 mm, was purchased from Jiangsu Aladdin High Temperature Materials Co., Ltd.

[0032] Preparation Example 1 Preparation of Ceramic Silica Gel

[0033] Here’s how:

[0034] S1. Modification of silicon nitride: 10 parts by weight of silicon nitride powder was added to 100 parts by weight of an ethanol solution containing 10 wt% hydrochloric acid, stirred at 35 ° C for 0.5 h, ball milled for 1 h to obtain a slurry, spray dried to obtain modified silicon nitride powder;

[0035] S2. Preparation of modified silica sol: 12 parts by weight of ethyl orthosilicate was dissolved in 200 parts by weight of ethanol, 3 parts by weight of modified silicon nitride obtained in step S1, 0.5 parts by weight of a sintering aid were added dropwise, 15 parts by weight of water was added, and the mixture was hydrolyzed at 40 ° C with stirring for 5 h to form a modified silica sol;

[0036] The sintering aids are aluminum oxide and silicon carbide, with a mass ratio of 4:2;

[0037] S3. Preparation of ceramic silica gel: 10 parts by weight of 100 g / m 2 The ceramic fiber paper is immersed in 100 parts by weight of the modified silica sol obtained in step S2, taken out after being completely soaked, dried, and repeatedly soaked until the fiber paper reaches 150 g / m 2 , take out, dry, and sinter at 800℃ for 2h to obtain ceramic silica gel.

[0038] Preparation Example 2 Preparation of Ceramic Silica Gel

[0039] Here’s how:

[0040] S1. Modification of silicon nitride: 10 parts by weight of silicon nitride powder was added to 100 parts by weight of an ethanol solution containing 15 wt% sulfuric acid, stirred at 45 ° C for 1 h, ball milled for 2 h to obtain a slurry, spray dried to obtain modified silicon nitride powder;

[0041] S2. Preparation of modified silica sol: 15 parts by weight of ethyl orthosilicate was dissolved in 200 parts by weight of ethanol, 5 parts by weight of modified silicon nitride obtained in step S1, 1 part by weight of a sintering aid were added dropwise, 20 parts by weight of water was added, and the mixture was hydrolyzed at 50 ° C with stirring for 7 h to form a modified silica sol;

[0042] The sintering aids are aluminum oxide and silicon carbide, with a mass ratio of 7:2;

[0043] S3. Preparation of ceramic silica gel: 10 parts by weight of 100 g / m 2 The ceramic fiber paper is immersed in 100 parts by weight of the modified silica sol obtained in step S2, taken out after being completely soaked, dried, and repeatedly soaked until the fiber paper reaches 150 g / m 2 , take out, dry, and sinter at 1000℃ for 4h to obtain ceramic silica gel.

[0044] Preparation Example 3 Preparation of Ceramic Silica Gel

[0045] Here’s how:

[0046] S1. Modification of silicon nitride: 10 parts by weight of silicon nitride powder was added to 100 parts by weight of an ethanol solution containing 12 wt% hydrochloric acid, stirred at 40 ° C for 1 h, ball milled for 1.5 h to obtain a slurry, spray dried to obtain modified silicon nitride powder;

[0047] S2. Preparation of modified silica sol: 13 parts by weight of ethyl orthosilicate was dissolved in 200 parts by weight of ethanol, 4 parts by weight of modified silicon nitride obtained in step S1, 0.7 parts by weight of a sintering aid were added dropwise, 17 parts by weight of water was added, and the mixture was hydrolyzed at 45 ° C with stirring for 6 h to form a modified silica sol;

[0048] The sintering aids are aluminum oxide and silicon carbide, with a mass ratio of 6:2;

[0049] S3. Preparation of ceramic silica gel: 10 parts by weight of 100 g / m 2 The ceramic fiber paper is immersed in 100 parts by weight of the modified silica sol obtained in step S2, taken out after being completely soaked, dried, and repeatedly soaked until the fiber paper reaches 150 g / m 2 , take out, dry, and sinter at 900℃ for 3h to obtain ceramic silica gel.

[0050] Preparation Example 4

[0051] Compared with Preparation Example 3, the difference is that the sintering aid is a single aluminum oxide.

[0052] Preparation Example 5

[0053] Compared with Preparation Example 3, the difference is that the sintering aid is a single silicon carbide.

[0054] Comparative Preparation Example 1

[0055] Compared with Preparation Example 3, the difference is that step S1 is not performed.

[0056] The details are as follows:

[0057] S1. Preparation of modified silica sol: 13 parts by weight of ethyl orthosilicate was dissolved in 200 parts by weight of ethanol, 4 parts by weight of silicon nitride, 0.7 parts by weight of a sintering aid were added, 17 parts by weight of water were added dropwise, and the mixture was stirred and hydrolyzed at 45°C for 6h to form a modified silica sol;

[0058] The sintering aids are aluminum oxide and silicon carbide, with a mass ratio of 6:2;

[0059] S2. Preparation of ceramic silica gel: 10 parts by weight of 100 g / m 2 The ceramic fiber paper is immersed in 100 parts by weight of the modified silica sol obtained in step S1, taken out after being completely soaked, dried, and repeatedly soaked until the fiber paper reaches 150 g / m 2 , take out, dry, and sinter at 900℃ for 3h to obtain ceramic silica gel.

[0060] Comparative Preparation Example 2

[0061] Compared with Preparation Example 3, the difference is that no sintering aid is added in step S2.

[0062] The details are as follows:

[0063] S2. Preparation of modified silica sol: 13 parts by weight of ethyl orthosilicate was dissolved in 200 parts by weight of ethanol, 4.7 parts by weight of modified silicon nitride obtained in step S1 was added, 17 parts by weight of water was added dropwise, and the mixture was stirred and hydrolyzed at 45°C for 6 hours to form a modified silica sol.

[0064] Comparative Preparation Example 3

[0065] Compared with Preparation Example 3, the difference is that no modified silicon nitride is added in step S2.

[0066] The details are as follows:

[0067] S2. Preparation of modified silica sol: 13 parts by weight of ethyl orthosilicate was dissolved in 200 parts by weight of ethanol, 4.7 parts by weight of sintering aid was added, 17 parts by weight of water was added dropwise, and the mixture was stirred and hydrolyzed at 45°C for 6 hours to form a modified silica sol.

[0068] Test Example 1

[0069] The ceramic silica gels prepared in Preparation Examples 1-5 of the present invention and Comparative Preparation Examples 1-3 were subjected to performance tests, and the results are shown in Table 1.

[0070] Hardness: Tested on a Shore A hardness tester according to GB / T531-2008 test method;

[0071] Tensile strength: According to the GB / T528-2009 test method, the tensile strength of the sample is tested using a tensile testing machine;

[0072] Flame retardancy: The flame retardancy of the test sample with a thickness of 2 mm was tested according to the UL94-2009 standard.

[0073] Ceramic test: Place the 2 mm thick test piece in a muffle furnace at 700 °C for 2 hours, collect the falling powder by vibration, and calculate the vibration shedding rate (by weight).

[0074] Vibration shedding rate (%) = shedding powder / initial weight × 100%

[0075] Table 1

[0076] Group Hardness(Shore A) Tensile strength(MPa) UL-94 Rating Vibration shedding rate (%) Preparation Example 1 92 5.1 V-0 0.17 Preparation Example 2 91 5.4 V-0 0.22 Preparation Example 3 94 5.5 V-0 0.14 Preparation Example 4 85 3.7 V-1 0.79 Preparation Example 5 82 4.5 V-0 1.52 Comparative Preparation Example 1 88 1.6 V-0 0.32 Comparative Preparation Example 2 78 3.1 V-1 2.29 Comparative Preparation Example 3 80 1.1 V-1 0.97

[0077] It can be seen from the above table that the ceramic silica gel prepared in Preparation Examples 1-3 of the present invention has good hardness, tensile strength, flame retardancy, and low vibration shedding rate.

[0078] Preparation Example 6 Preparation of modified PVC material

[0079] Here’s how:

[0080] T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: 0.5 parts by weight of cerium chloride and 0.2 parts by weight of lanthanum chloride were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 12 parts by weight of tetrabutyl titanate and 7 parts by weight of aluminum isopropoxide, stirred at 30°C for 2h, ball milled for 1h, spray dried, and calcined at 400°C for 1h to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials;

[0081] T2 modification: 100 parts by weight of the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial prepared in step T1 was added to 300 parts by weight of water, 7 parts by weight of a composite silane coupling agent was added, heated to 40 ° C, stirred for 1h, centrifuged, washed, and dried to obtain a modified nanomaterial;

[0082] The composite silane coupling agent is a mixture of octadecylethoxysilane and KH792, with a mass ratio of 7:12;

[0083] T3 flame retardant modification: 100 parts by weight of the modified nanomaterial obtained in step T2 was added to 200 parts by weight of dichloromethane, and 3 parts by weight of phenylphosphoryl dichloride was added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the mixture was heated to 55 ° C, stirred for 5h, centrifuged, washed, and dried to obtain a flame retardant modified nanomaterial;

[0084] T4. Preparation of modified PVC material: 12 parts by weight of the flame-retardant modified nanomaterial obtained in step T3 and 150 parts by weight of PVC resin were heated to 250° C. and melt-blended for 1 hour, extruded and granulated to obtain a modified PVC material.

[0085] Preparation Example 7 Preparation of modified PVC material

[0086] Here’s how:

[0087] T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: 1 part by weight of cerium nitrate and 0.4 parts by weight of lanthanum nitrate were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 15 parts by weight of tetrabutyl titanate and 10 parts by weight of aluminum isopropoxide, stirred at 40°C for 4 hours, ball milled for 2 hours, spray dried, and calcined at 600°C for 3 hours to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials;

[0088] T2 modification: 100 parts by weight of the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial prepared in step T1 was added to 300 parts by weight of water, 10 parts by weight of a composite silane coupling agent was added, heated to 50 ° C, stirred for 3h, centrifuged, washed, and dried to obtain a modified nanomaterial;

[0089] The composite silane coupling agent is a mixture of octadecylethoxysilane and KH792, with a mass ratio of 10:15;

[0090] T3 flame retardant modification: 100 parts by weight of the modified nanomaterial obtained in step T2 was added to 200 parts by weight of dichloromethane, and 5 parts by weight of phenylphosphoryl dichloride was added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the mixture was heated to 65 ° C, stirred for 7h, centrifuged, washed, and dried to obtain a flame retardant modified nanomaterial;

[0091] T4. Preparation of modified PVC material: 15 parts by weight of the flame-retardant modified nanomaterial obtained in step T3 and 150 parts by weight of PVC resin were heated to 270°C and melt-blended for 3 hours, extruded and granulated to obtain a modified PVC material.

[0092] Preparation Example 8 Preparation of modified PVC material

[0093] Here’s how:

[0094] T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: 0.7 parts by weight of cerium nitrate and 0.3 parts by weight of lanthanum nitrate were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 13 parts by weight of tetrabutyl titanate and 8 parts by weight of aluminum isopropoxide, stirred at 35°C for 3 hours, ball milled for 1.5 hours, spray dried, and calcined at 500°C for 2 hours to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials;

[0095] T2 modification: 100 parts by weight of the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial prepared in step T1 was added to 300 parts by weight of water, 8 parts by weight of a composite silane coupling agent was added, heated to 45 ° C, stirred for 2h, centrifuged, washed, and dried to obtain a modified nanomaterial;

[0096] The composite silane coupling agent is a mixture of octadecylethoxysilane and KH792, with a mass ratio of 8:13;

[0097] T3 flame retardant modification: 100 parts by weight of the modified nanomaterial obtained in step T2 was added to 200 parts by weight of dichloromethane, and 4 parts by weight of phenylphosphoryl dichloride was added dropwise at 0 ° C under nitrogen protection. After the addition was completed, the mixture was heated to 60 ° C, stirred for 6 hours, centrifuged, washed, and dried to obtain a flame retardant modified nanomaterial;

[0098] T4. Preparation of modified PVC material: 13 parts by weight of the flame-retardant modified nanomaterial obtained in step T3 and 150 parts by weight of PVC resin were heated to 260°C and melt-blended for 2h, extruded and granulated to obtain a modified PVC material.

[0099] Preparation Example 9

[0100] Compared with Preparation Example 8, the difference is that the composite silane coupling agent is a single octadecylethoxysilane.

[0101] Preparation Example 10

[0102] Compared with Preparation Example 8, the difference is that the composite silane coupling agent is a single KH792.

[0103] Comparative Preparation Example 4

[0104] Compared with Preparation Example 8, the difference is that cerium nitrate is not added in step T1.

[0105] The details are as follows:

[0106] T1. Preparation of lanthanum-doped titanium oxide / aluminum oxide nanomaterials: Dissolve 1 part by weight of lanthanum nitrate in 100 parts by weight of water, add to 200 parts by weight of ethanol solution containing 13 parts by weight of tetrabutyl titanate and 8 parts by weight of aluminum isopropoxide, stir and react at 35°C for 3 hours, ball mill for 1.5 hours, spray dry, and calcine at 500°C for 2 hours to obtain lanthanum-doped titanium oxide / aluminum oxide nanomaterials.

[0107] Comparative Preparation Example 5

[0108] Compared with Preparation Example 8, the difference is that lanthanum nitrate is not added in step T1.

[0109] The details are as follows:

[0110] T1. Preparation of cerium-doped titanium oxide / aluminum oxide nanomaterials: Dissolve 1 part by weight of cerium nitrate in 100 parts by weight of water, add to 200 parts by weight of ethanol solution containing 13 parts by weight of tetrabutyl titanate and 8 parts by weight of aluminum isopropoxide, stir and react at 35°C for 3 hours, ball mill for 1.5 hours, spray dry, and calcine at 500°C for 2 hours to obtain cerium-doped titanium oxide / aluminum oxide nanomaterials.

[0111] Comparative Preparation Example 6

[0112] Compared with Preparation Example 8, the difference is that cerium nitrate and lanthanum nitrate are not added in step T1.

[0113] The details are as follows:

[0114] T1. Preparation of titanium oxide / aluminum oxide nanomaterials: Add 200 parts by weight of an ethanol solution containing 13 parts by weight of tetrabutyl titanate and 8 parts by weight of aluminum isopropoxide to 100 parts by weight of water, stir and react at 35°C for 3 hours, ball mill for 1.5 hours, spray dry, and calcine at 500°C for 2 hours to obtain titanium oxide / aluminum oxide nanomaterials.

[0115] Comparative Preparation Example 7

[0116] Compared with Preparation Example 8, the difference is that tetrabutyl titanate is not added in step T1.

[0117] The details are as follows:

[0118] T1. Preparation of cerium / lanthanum doped alumina nanomaterials: 0.7 parts by weight of cerium nitrate and 0.3 parts by weight of lanthanum nitrate were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 21 parts by weight of aluminum isopropoxide, stirred at 35°C for 3 hours, ball milled for 1.5 hours, spray dried, and calcined at 500°C for 2 hours to obtain cerium / lanthanum doped alumina nanomaterials.

[0119] Comparative Preparation Example 8

[0120] Compared with Preparation Example 8, the difference is that aluminum isopropoxide is not added in step T1.

[0121] The details are as follows:

[0122] T1. Preparation of cerium / lanthanum doped titanium oxide nanomaterials: 0.7 parts by weight of cerium nitrate and 0.3 parts by weight of lanthanum nitrate were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 21 parts by weight of tetrabutyl titanate, stirred at 35°C for 3 hours, ball milled for 1.5 hours, spray dried, and calcined at 500°C for 2 hours to obtain cerium / lanthanum doped titanium oxide nanomaterials.

[0123] Comparative Preparation Example 9

[0124] Compared with Preparation Example 8, the difference is that steps T2 and T3 are not performed.

[0125] The details are as follows:

[0126] T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: 0.7 parts by weight of cerium nitrate and 0.3 parts by weight of lanthanum nitrate were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 13 parts by weight of tetrabutyl titanate and 8 parts by weight of aluminum isopropoxide, stirred at 35°C for 3 hours, ball milled for 1.5 hours, spray dried, and calcined at 500°C for 2 hours to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials;

[0127] T2. Preparation of modified PVC material: 13 parts by weight of the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial prepared in step T1 and 150 parts by weight of PVC resin were heated to 260°C and melt-blended for 2 hours, extruded and granulated to obtain a modified PVC material.

[0128] Comparative Preparation Example 10

[0129] Compared with Preparation Example 8, the difference is that step T3 is not performed.

[0130] The details are as follows:

[0131] T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: 0.7 parts by weight of cerium nitrate and 0.3 parts by weight of lanthanum nitrate were dissolved in 100 parts by weight of water, added to 200 parts by weight of an ethanol solution containing 13 parts by weight of tetrabutyl titanate and 8 parts by weight of aluminum isopropoxide, stirred at 35°C for 3 hours, ball milled for 1.5 hours, spray dried, and calcined at 500°C for 2 hours to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials;

[0132] T2 modification: 100 parts by weight of the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial prepared in step T1 was added to 300 parts by weight of water, 8 parts by weight of a composite silane coupling agent was added, heated to 45 ° C, stirred for 2h, centrifuged, washed, and dried to obtain a modified nanomaterial;

[0133] The composite silane coupling agent is a mixture of octadecylethoxysilane and KH792, with a mass ratio of 8:13;

[0134] T3. Preparation of modified PVC material: 13 parts by weight of the modified nanomaterial obtained in step T2 and 150 parts by weight of PVC resin were heated to 260°C and melt-blended for 2h, extruded and granulated to obtain a modified PVC material.

[0135] Test Example 1

[0136] The modified PVC materials prepared in Preparation Examples 6-10 and Comparative Preparation Examples 4-10 were subjected to performance tests. The results are shown in Table 2.

[0137] Tensile performance test: The tensile test was carried out in accordance with GB / T1040.1-2018 standard. The tensile specimen adopted a standard dumbbell shape with a length of 115 mm, a gauge length of 25 mm, and an effective width of 6 mm. The tensile speed was 500 mm / min at room temperature.

[0138] Aging resistance test: According to GB / T16422.3-2022, the modified PVC material was subjected to UV aging, and a three-stage cycle of fluorescent UV light irradiation for 8 hours, spraying for 0.25 hours, and condensation for 3.75 hours was set to simulate the natural aging process of the sample. In the fluorescent UV light irradiation stage, the UV wavelength was 320-360nm, the temperature was 52°C, and the irradiation intensity was 0.76W / m 2 There was no UV irradiation during the spraying and condensation stages, the temperature was 30°C, and the sample aging time was 240h. The tensile properties of the material after aging were tested.

[0139] Water-oil contact angle: The contact angle was characterized by using a DSA-25 contact angle tester produced by Kruess GmbH of Germany (water and hexadecane were used as media). The sample was pressed into tablets and tested 5 times to obtain the average value.

[0140] Limiting oxygen index (LOI) test: measured in accordance with ISO4589-2, sample size is 100×6.5×2mm 3 .

[0141] Vertical burning test (UL94): tested according to UL94-2009 standard, sample size is 130×13×3mm 3 .

[0142] Table 2

[0143]

[0144]

[0145] It can be seen from the above table that the modified PVC materials prepared in Preparation Examples 6-8 of the present invention have good tensile properties, aging resistance, hydrophobic and oleophobic properties, and flame retardant properties.

[0146] Example 1

[0147] This embodiment provides a fire-proof, short-circuit-proof and aging-proof wire and cable, comprising a copper body, a coating layer made of ceramic silicone prepared in Preparation Example 1 coated on the copper body, with a thickness of 2 mm, and a coating layer made of modified PVC material prepared in Preparation Example 6 coated on the ceramic silicone layer, with a thickness of 1.5 mm.

[0148] Example 2

[0149] This embodiment provides a fire-proof, short-circuit-proof and aging-proof wire and cable, comprising a copper body, a coating layer made of ceramic silicone prepared in Preparation Example 2 coated on the copper body, with a thickness of 2 mm, and a coating layer made of modified PVC material prepared in Preparation Example 7 coated on the ceramic silicone layer, with a thickness of 1.5 mm.

[0150] Example 3

[0151] This embodiment provides a fire-proof, short-circuit-proof and aging-proof wire and cable, comprising a copper body, a coating layer made of ceramic silica gel prepared in Preparation Example 3 coated on the copper body, with a thickness of 2 mm, and a coating layer made of modified PVC material prepared in Preparation Example 8 coated on the ceramic silica gel layer, with a thickness of 1.5 mm.

[0152] Example 4

[0153] Compared with Example 3, the difference is that the ceramic silica gel is prepared by Preparation Example 4.

[0154] Example 5

[0155] Compared with Example 3, the difference is that the ceramic silica gel is prepared by Preparation Example 5.

[0156] Example 6

[0157] Compared with Example 3, the difference is that the modified PVC material is prepared by Preparation Example 9.

[0158] Example 7

[0159] Compared with Example 3, the difference is that the modified PVC material is prepared by Preparation Example 10.

[0160] Comparative Example 1

[0161] Compared with Example 3, the difference is that the ceramic silica gel is prepared by Comparative Preparation Example 1.

[0162] Comparative Example 2

[0163] Compared with Example 3, the difference is that the ceramic silica gel is prepared by Comparative Preparation Example 2.

[0164] Comparative Example 3

[0165] Compared with Example 3, the difference is that the ceramic silica gel is prepared by Comparative Preparation Example 3.

[0166] Comparative Example 4

[0167] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 4.

[0168] Comparative Example 5

[0169] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 5.

[0170] Comparative Example 6

[0171] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 6.

[0172] Comparative Example 7

[0173] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 7.

[0174] Comparative Example 8

[0175] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 8.

[0176] Comparative Example 9

[0177] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 9.

[0178] Comparative Example 10

[0179] Compared with Example 3, the difference is that the modified PVC material is prepared by Comparative Preparation Example 10.

[0180] Test Example 3

[0181] The fireproof, short-circuit-proof and aging-proof electric wires and cables prepared in Examples 1-7 and Comparative Examples 1-10 of the present invention were tested according to BS6387-2013. The results are shown in Table 3.

[0182] BS6387 Class C fire resistant cable test: withstand 950°C flame for 180 minutes.

[0183] BS6387 W class fire resistant cable test: withstand 650℃ flame for 15 minutes and water spray for 15 minutes.

[0184] BS6387 Z class fire resistant cable test: withstand 950℃ flame burning and mechanical impact for 15 minutes.

[0185] Table 3

[0186] Group Class C fire-resistant cable assessment W Class Fire Resistant Cable Assessment Class Z fire-resistant cable assessment Example 1 pass pass pass Example 2 pass pass pass Example 3 pass pass pass Example 4 pass pass Not passed Example 5 pass pass Not passed Example 6 pass pass pass Example 7 pass pass Not passed Comparative Example 1 pass pass pass Comparative Example 2 pass pass Not passed Comparative Example 3 Not passed pass Not passed Comparative Example 4 pass pass pass Comparative Example 5 pass pass pass Comparative Example 6 pass pass pass Comparative Example 7 pass pass pass Comparative Example 8 pass pass Not passed Comparative Example 9 Not passed pass Not passed Comparative Example 10 Not passed pass Not passed

[0187] It can be seen from the above table that the fire-proof, short-circuit-proof and aging-proof wires and cables prepared in Examples 1-3 of the present invention meet the three CWZ assessments of BS6387-2013.

[0188] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A fire-proof, short-circuit-proof and aging-proof electric wire and cable, characterized in that: The invention comprises a copper body, a ceramic silica gel layer coated on the copper body, and a modified PVC material layer coated on the ceramic silica gel layer; the ceramic silica gel layer is prepared by adhering silicon nitride and sintering modified silica sol on the surface of ceramic fiber paper and sintering; the modified PVC material layer is prepared by modifying the surface of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterial with a silane coupling agent, reacting with phenylphosphinoyl dichloride, adding PVC material and melt blending; the silane coupling agent is a mixture of octadecylethoxysilane and KH792; The preparation method of the ceramic silica gel is as follows: S1. Modification of silicon nitride: adding silicon nitride powder to an acid solution, stirring the reaction, ball milling to obtain a grinding slurry, spray drying, and obtaining a modified silicon nitride powder; S2. Preparation of modified silica sol: dissolving tetraethyl orthosilicate in ethanol, adding the modified silicon nitride and sintering aid obtained in step S1, dropping water, stirring and hydrolyzing to form a modified silica sol; the sintering aid is alumina and silicon carbide; S3. Preparation of ceramic silica gel: Immerse the ceramic fiber paper in the modified silica sol obtained in step S2, take it out after it is completely soaked, dry it, and repeat the soaking, taking it out, drying it, and sintering it to obtain ceramic silica gel.

2. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 1 is characterized in that: In step S1, the acid solution is an ethanol solution containing 10-15 wt% hydrochloric acid or sulfuric acid, the stirring reaction temperature is 35-45°C, the time is 0.5-1h, and the ball milling time is 1-2h.

3. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 1 is characterized in that: The mass ratio of tetraethyl orthosilicate, ethanol, modified silicon nitride, sintering aid and water in step S2 is 12-15:200:3-5:0.5-1:15-20, the stirring hydrolysis temperature is 40-50°C, the time is 5-7h, and the mass ratio of aluminum oxide and silicon carbide in the sintering aid is 4-7:

2.

4. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 1, characterized in that: The ceramic fiber paper in step S3 is 90-110 g / m 2 Repeat the impregnation until the fiber paper reaches 130-150g / m 2 The sintering temperature is 800-1000°C and the sintering time is 2-4h.

5. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 1 is characterized in that: The preparation method of the modified PVC material is as follows: T1. Preparation of cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials: dissolving cerium salt and lanthanum salt in water, adding to an ethanol solution containing tetrabutyl titanate and aluminum isopropoxide, stirring for reaction, ball milling, spray drying, and calcining to obtain cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterials; T2. Modification: adding the cerium / lanthanum-doped titanium oxide / aluminum oxide nanomaterial obtained in step T1 to water, adding a composite silane coupling agent, heating and stirring the reaction, centrifuging, washing, and drying to obtain a modified nanomaterial; T3 flame retardant modification: the modified nanomaterial obtained in step T2 is added to dichloromethane, phenylphosphoryl dichloride is added dropwise, the reaction is heated and stirred under inert gas protection, centrifuged, washed, and dried to obtain a flame retardant modified nanomaterial; T4. Preparation of modified PVC material: melt-blending the flame-retardant modified nanomaterial obtained in step T3 and PVC resin, extruding and granulating, to obtain a modified PVC material.

6. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 5, characterized in that: In step T1, the cerium salt is selected from at least one of cerium chloride and cerium nitrate, the lanthanum salt is selected from at least one of lanthanum chloride and lanthanum nitrate, the mass ratio of the cerium salt, lanthanum salt, tetrabutyl titanate, and aluminum isopropoxide is 0.5-1:0.2-0.4:12-15:7-10, the stirring reaction temperature is 30-40°C, the time is 2-4h, the ball milling time is 1-2h, and the calcination temperature is 400-600°C, and the time is 1-3h.

7. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 5, characterized in that: In step T2, the mass ratio of the cerium / lanthanum doped titanium oxide / aluminum oxide nanomaterial and the composite silane coupling agent is 100:7-10, the composite silane coupling agent includes a long-chain alkyl silane coupling agent and a silane coupling agent with an amino group, the long-chain alkyl silane coupling agent is selected from at least one of dodecyl methoxy silane, dodecyl ethoxy silane, tetradecyl methoxy silane, tetradecyl ethoxy silane, hexadecyl ethoxy silane and octadecyl ethoxy silane, the composite silane coupling agent is a mixture of octadecyl ethoxy silane and KH792, the mass ratio is 7-10:12-15, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-3h.

8. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 5, characterized in that: The mass ratio of the modified nanomaterial and phenylphosphoryl dichloride in step T3 is 100:3-5, the temperature of the heating and stirring reaction is 55-65°C, and the time is 5-7h; the mass ratio of the flame retardant modified nanomaterial and PVC resin in step T4 is 12-15:150, the temperature of the melt blending is 250-270°C, and the time is 1-3h.

9. The fireproof, short-circuit-proof and aging-proof electric wire and cable according to claim 1, characterized in that: The thickness of the ceramic silicone layer is 1.5-2.5 mm, and the thickness of the modified PVC material layer is 1-2 mm.

Citation Information

Patent Citations

  • Continuous casting tundish coating

    CN106747342A

  • Cable and optical cable data cable integration bus and preparation method thereof

    CN106876026A